Ana CALVO REVILLA, ed., "Elogio de lo mínimo. Estudios sobre microrrelato y minificción en el siglo XXI". Madrid-Frankfurt, Iberoamericana-Vervuert, 2018, 314 pp.: Estudios sobre microrrelato y minificción en el siglo XXI - Solano Conde, María (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
In the collective book she coordinates, Ana Calvo Revilla approaches the state of mini-fiction and micro-stories in the context of digital culture, with the implications that this ecosystem has entailed in the processes of creation, reception and broadcasting of literary works.